Phenyl bis(morpholin-4-ylamido)phosphinate - Pourayoubi, Mehrdad (International Union of Crystallography, 2011)
In the title compound, C(14)H(23)N(4)O(4)P, the P atom is in a distorted tetrahedral environment with bond angles in the range 96.87 (6)–119.86 (6)°. The two morpholinyl groups adopt a chair conformation. The phenyl ring is disordered over two sets of sites with equal occupancies [0.500 (2)]. In the crystal, adjacent molecules are linked via N—H⋯O hydrogen bonds into an extended chain running parallel to the a axis. Only one of the amidate N—H groups is involved in hydrogen bonding.